Contexto, prática e obstáculos do acesso a informação: insumos para a discussão a partir da experiência com o setor nuclear brasileiro - Cruz, Isabela de Paula (2018)
The experience of making almost one hundred requests to the Brazilian nuclear sector, considered one of the most sensitive and strategic in Brazil, made it possible to develop a qualitative and juridical analysis of the context, practices and obstacles of access to information in the area of Federal Administration. The recommendations resulting from that examination may apply to a number of other sectors, as those recommendations have taken into account the maximum obstacles to the implementation of open government. The research uses concepts of Law and Political Science, with a view to analyzing qualitatively (i) how the structure of the access policy is mobilized by the public machine when it receives requests for access to information; (ii) what the biggest obstacles to access are; and (iii) what practices can be adopted to make the Brazilian state more transparent. The first chapter looks at the new forms of legitimacy of contemporary democracy and demonstrates the importance of improving access to information for maintaining a healthy political regime—capable of dealing with the aspirations of today's society for political participation, not only in electoral terms, but also in its monitory dimension. The second chapter contextualizes the access to information in Brazil and reflects on the specific challenges of the nuclear sector, dealing with theoretical and historical aspects and systematizing the norms that rule the subjects of transparency and the protection of confidential information. The panorama indicates that Law 12,527/2011 is referenced very little in lawsuits, although it is already part of the routine of the Executive Power, at least when involving the organs and entities linked in some way to the Brazilian Nuclear Program. Finally, the third chapter contrasts with the optimism that could arise from a quantitative analysis of the responsiveness of the Federal Administration to requests for access, revealing several obstacles to passive transparency. The recommendations presented concern (i) the need to motivate the denial of access; (ii) the ongoing decisionmaking processes that are forever under secrecy; (iii) the absence of anonymity in the Brazilian system of access to information; (iv) the impossibility of consulting or of having any form of interested third parties’ intervention; and (v) the successive referrals and their consequences to the procedural deadlines.